2016
DOI: 10.1371/journal.pone.0150897
|View full text |Cite
|
Sign up to set email alerts
|

Role of IGFBP7 in Diabetic Nephropathy: TGF-β1 Induces IGFBP7 via Smad2/4 in Human Renal Proximal Tubular Epithelial Cells

Abstract: Tubular injury is one of the important determinants of progressive renal failure in diabetic nephropathy (DN), and TGF-β1 has been implicated in the pathogenesis of tubulointerstitial disease that characterizes proteinuric renal disease. The aim of this study was to identify novel therapeutic target molecules that play a role in the tubule damage of DN. We used an LC-MS/MS-based proteomic technique and human renal proximal epithelial cells (HRPTECs). Urine samples from Japanese patients with type 2 diabetes (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 52 publications
(54 reference statements)
2
35
1
Order By: Relevance
“…[1] Tubular injury plays a critical role in DKD progression, which correlates with renal functional deterioration, a primary change associated with the disease. [2] The pathogenesis of DKD is not clear, but mitochondrial abnormalities largely contribute to its development. [[3], [5]].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Tubular injury plays a critical role in DKD progression, which correlates with renal functional deterioration, a primary change associated with the disease. [2] The pathogenesis of DKD is not clear, but mitochondrial abnormalities largely contribute to its development. [[3], [5]].…”
Section: Introductionmentioning
confidence: 99%
“…Expression has also been reported in proximal tubule cells, but primarily only in response to insults, mitogens, or second messengers (14,20,41,45,62,63). There is a dearth of information regarding IGFBP7 in the kidney, and what is available is contradictory, showing expression in the glomerulus and alternatively in distal and proximal tubule cells (17,35,42,65,72).…”
mentioning
confidence: 99%
“…It has been reported that ECM components such as collagen, broblasts and their associated signaling molecules contribute to tumor cell proliferation, migration and invasion in various cancers [40,41]. Moreover, IGFBP7 has been reported to regulate epithelial-mesenchylmal transition (EMT) in some solid tumors [12,42,43]. The above results suggest that IGFBP7 and its coexpressed genes may be involved in ECM-related pathways, which would contribute to the utility of IGFBP7 to predict poor prognosis of GC.…”
Section: Discussionmentioning
confidence: 87%